The Interaction of von Willebrand Factor (vWf) with Collagen: Investigation of vWf-Binding Sites in the Collagen Molecule - Fitzsimmons, C M; Cockburn, C G; Hornsey, V; Prowse, C V; Barnes, M J (Thrombosis and Haemostasis, 1988)
Following fragmentation of the collagen molecule, we have examined the ability of the isolated fragments to bind vWf. In view of the importance of collagen tertiary and quaternary structure for binding, fragments were first renatured to restore triple-helical conformation and then polymerized. Results indicate the presence of specific vWf-binding sites in both the αl(I)-and α2(I)-chains of type I collagen. Cleavage of the αl(I)-chain with cyanogen bromide suggests the presence of at least four (conceivably several more) binding sites implying a wide distribution of sites along the length of the collagen type I molecule. Collagen type III appears to possess a similar wide distribution of sites. Chemical modification of specific amino acid residues indicates that interaction involves arginyl residues in collagen and carboxyl groups in vWf. Although interaction between fibronec-tin and collagen fibres also involves collagen arginyl residues and carboxyl groups in fibronectin (authors’ unpublished results), fibronectin does not compete with vWf in the binding to collagen fibres.
Keywords: Collagen; von Willebrand factor; Fibronectin